2014
DOI: 10.1038/srep05955
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular iron diminishes anticancer effects of vitamin C: An in vitro study

Abstract: In vitro studies have shown that hydrogen peroxide (H2O2) produced by high-concentration ascorbate and cell culture medium iron efficiently kills cancer cells. This provided the rationale for clinical trials of high-dose intravenous ascorbate-based treatment for cancer. A drawback in all the in vitro studies was their failure to take into account the in vivo concentration of iron to supplement cell culture media which are characterized by low iron content. Here we showed, using two prostate cancer cell lines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 58 publications
6
53
1
Order By: Relevance
“…This provides a mechanistic basis to apply pro-oxidative therapeutic strategies (such as high-dose ascorbate) to kill cancer cells using ROS-mediated mechanisms [18,19]. Thus, it seems plausible to assume that increasing ROS (superoxide) production and the labile iron pool in cancer cells may sensitize them to ascorbate [20]; however, extracellular iron at physiological conditions may also diminish the anticancer effects of ascorbate [21]. In line with this assumption, Levine and his group demonstrated in in vitro studies on 43 different cancer cell lines and five nontransformed somatic cell populations a preferential toxicity of ascorbate toward the cancer cells: an average IC 50 of < 10 mM ascorbate was detected in the cancer cells at incubation times of < 2 h, while the benign cells tolerated much higher doses of ascorbate [7].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…This provides a mechanistic basis to apply pro-oxidative therapeutic strategies (such as high-dose ascorbate) to kill cancer cells using ROS-mediated mechanisms [18,19]. Thus, it seems plausible to assume that increasing ROS (superoxide) production and the labile iron pool in cancer cells may sensitize them to ascorbate [20]; however, extracellular iron at physiological conditions may also diminish the anticancer effects of ascorbate [21]. In line with this assumption, Levine and his group demonstrated in in vitro studies on 43 different cancer cell lines and five nontransformed somatic cell populations a preferential toxicity of ascorbate toward the cancer cells: an average IC 50 of < 10 mM ascorbate was detected in the cancer cells at incubation times of < 2 h, while the benign cells tolerated much higher doses of ascorbate [7].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…However, our previous study reported that 5 mM AsA treatment suppressed the growth of epithelial cancer cells in vitro (6). It was suggested that extracellular H 2 O 2 generated with >5 mM AsA mainly damaged the cell membrane due to passing more cascades than radiation alone (19,20). The current study revealed that caspase-3, -8 and -9 were activated 2 h after exposure to H 2 O 2 , whereas in irradiated cells activation of caspase-3 and -9 occurred 4 h after exposure; caspase-8 activation was not observed (19).…”
Section: Discussionmentioning
confidence: 97%
“…However, in a recent study the cytotoxic effect was abolished at physiological concentrations of iron which prevented the accumulation of hydrogen peroxide [68]. It was suggested that previous studies disregarding in vivo concentration of iron had significantly overestimated the anticancer effect of AA [68].…”
Section: High Dose Intravenous Vitamin C (Ivc) Therapy In Cancermentioning
confidence: 94%
“…Cytotoxicity of AA to cancer cells was based on in vitro studies which suggested that AA in concentrations higher than physiological in the extracellular space act as a pro-oxidant and through the formation hydrogen peroxide kill cancer cells [67]. However, in a recent study the cytotoxic effect was abolished at physiological concentrations of iron which prevented the accumulation of hydrogen peroxide [68]. It was suggested that previous studies disregarding in vivo concentration of iron had significantly overestimated the anticancer effect of AA [68].…”
Section: High Dose Intravenous Vitamin C (Ivc) Therapy In Cancermentioning
confidence: 99%